EFEKTIFITAS KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP PENINGKATAN KINERJA GURU - FAHRINA YUSTIASARI LIRIWATI (Universitas Muhammadiyah Ponorogo, 2017)
Changes to a new paradigm of education management demand professionalism principal leadership. Through transformational leadership, principals should be able to optimize the potential of the school as well as possible. The leadership of the principal with regard to skills and competencies either principal or hard skill was to affect the entire school's resources to achieve the goals and objectives that have been set at school. An effective principal leadership is a leadership that is able to empower the entire potential at school with optimal, so teachers, staff, and other employees feel established by the school. Good leadership certainly very impacts on whether the objectives of the Organization are achieved because the leader has an impact on his performance.